Rumah Pintar Pemilu: Strategi peningkatan partisipasi pemilih pemula - yohana yulianti simbolon (Prodi Ilmu Komunikasi Universitas Putera Batam, 2019)
Election Smart House is a new innovation by the General Election Commission. Election Smart House in the form of utilization of space in the General Election Commission office which contains various knowledge about elections and democracy. The presence of Election Smart House at the district and provincial levels to provide knowledge about electoral and democracy to the community, especially beginner voters. So that it is expected to increase voter participation in the 2019 election. This study aims to determine the strategies carried out by the General Election Commission, specifically General Election Commission of Toba Samosir Regency in order to increase the participation of beginner voters through Election Smart House. This research method uses descriptive qualitative. The results of this study, Toba Samosir regency carried out a communication strategy by holding electoral classes whose participants came from schools and campuses but instead held outside the Election Smart House room. The researcher concluded that the Election Smart House activities and programs did not work properly due to several factors; first, lack of manager time due to being involved in the preparation of 2018 regional elections and 2019 elections. Second, lack of supporting staff who can assist managers in managing Election Smart House. The third is the lack of technical guidance facilities held by the Central General Election Commission or the Provincial General Election Commission on Election Smart House in General Election Commission Toba Samosir regency.